2014
DOI: 10.5070/d3206022869
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous thrombogenic vasculopathy associated with bevacizumab therapy

Abstract: Bevacizumab, a humanized monoclonal antibody against vascular endothelial growth factor (VEGF), is an angiogenesis inhibitor used to treat a variety of cancers, including lung, colon, cervical, ovarian, and renal cancers as well as glioblastoma. A significant adverse effect associated with its use is one of thromboembolic events. We report a case of a 74-year-old male with diagnosis of glioblastoma multiforme treated with partial resection, radiation, temozolomide, and bevacizumab. He presented to a plastic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…This result is similar to that of Hao et al suggesting that D‐dimer level could be used as a predictor for CRT 33 . The study of Kiuru et al showed that the role of VEGFI might include direct endothelial cell injury, induced platelet aggregation, and activation of FcγRIIa platelet receptors 34 . However, platelet aggregation led to a blood hypercoagulable state and thrombosis in susceptible patients, and its effect depends on FcγRIIa platelet receptors 35 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This result is similar to that of Hao et al suggesting that D‐dimer level could be used as a predictor for CRT 33 . The study of Kiuru et al showed that the role of VEGFI might include direct endothelial cell injury, induced platelet aggregation, and activation of FcγRIIa platelet receptors 34 . However, platelet aggregation led to a blood hypercoagulable state and thrombosis in susceptible patients, and its effect depends on FcγRIIa platelet receptors 35 .…”
Section: Discussionsupporting
confidence: 84%
“… 33 The study of Kiuru et al showed that the role of VEGFI might include direct endothelial cell injury, induced platelet aggregation, and activation of FcγRIIa platelet receptors. 34 However, platelet aggregation led to a blood hypercoagulable state and thrombosis in susceptible patients, and its effect depends on FcγRIIa platelet receptors. 35 In the study by Verso et al, the association between chest radiotherapy and CRT in patients with cancer was also observed.…”
Section: Discussionmentioning
confidence: 99%